OCT Angiography in Noninfectious Uveitis: A Description of Five Cases and Clinical Applications - Samyuktha Melachuri; Kunal K. Dansingani; Joshua Wesalo; Manuel Paez-Escamilla; Meghal Gagrani; Sarah Atta; Chad Indermill; José-Alain Sahel; Ken K. Nischal; Jay Chhablani; Marie-Hélène Errera (Diagnostics, 2023)
Background: Optical coherence tomography angiography (OCTA) is a noninvasive imaging modality used to analyze the retinochoroidal vasculature and detect vascular flow. The resulting images can be segmented to view each vascular plexus individually. While fluorescein angiography is still the gold standard for the diagnosis of posterior uveitis, it has limitations, and can be replaced by OCTA in some cases. Methods: This case series describes five patients with posterior noninfectious uveitis and their description by OCTA. Results: Cases included lupus retinopathy (n = 1) for which OCTA showed ischemic maculopathy as areas of flow deficit at the superficial and deep capillary plexus; choroidal granulomas (n = 1) with a non-detectable flow signal in the choroid; active punctate inner choroiditis and multifocal choroiditis (n = 1) with OCTA that showed active inflammatory chorioretinal lesions as non-detectable flow signals in choriocapillaris and choroid; dense type 2 inflammatory secondary neovascularization (n = 1) associated with active choroiditis; and acute posterior multifocal placoid pigment epitheliopathy (APMPPE) (n = 1) without flow abnormalities at the superficial and deep retinal plexuses but non-detectable flow at the levels of the choriocapillaris and choroid. Conclusions: Ophthalmologists can use OCTA to identify inflammatory changes in retinal and choroidal vasculature, aiding in the diagnosis, management, and monitoring of posterior uveitis.